Coordinate Systems Integration for Craniofacial Database from Multimodal Devices - Deni Suwardhi; Halim Setan; Albert K. Chong; Zainul Rajion (Institute for Research and Community Services, Institut Teknologi Bandung, 2005)
This study presents a data registration method for craniofacial spatial data of different modalities. The data consists of three dimensional (3D) vector and raster data models. The data is stored in object relational database. The data capture devices are Laser scanner, CT (Computed Tomography) scan and CR (Close Range) Photogrammetry. The objective of the registration is to transform the data from various coordinate systems into a single 3-D Cartesian coordinate system. The standard error of the registration obtained from multimodal imaging devices using 3D affine transformation is in the ranged of 1-2 mm. This study is a step forward for storing the craniofacial spatial data in one reference system in database.